3D printing performance of gels from wheat starch, flour and whole meal. (15th September 2021) - Zheng, Luyao; Liu, Junbo; Liu, Rui; Xing, Yanan; Jiang, Hao
Highlights: 3D printing performance of wheat-based gels was affected by materials' components. Physicochemical and structural properties about the printed samples were assayed. LF-NMR can be used to explore changes of water distribution during storage. Abstract: The effects of material composition on the quality of 3D-printed food using wheat starch, flour and whole meal were explored. Results showed that samples molded by wheat starch and whole meal obtained a more accurate and better quality printing than wheat flour. Wheat flour had the worst printable capacity as it gets stuck easily to the wall of the printer. Starch-protein complexes appeared in the samples of wheat flour and whole meal. Whole meal constituted protein, fat, fiber and starch to form various complexes, which strengthen the gel network cross-linking, retard starch aging significantly, and enhance the water binding capacity than just the starch only sample. Printed samples using whole meal still possess a soft and elastic texture after long-time storage. Overall, whole meal with higher protein, fat and fiber content was better for food 3D printing than wheat starch and flour.